The Improvement of the Estate A Study of Jane Austen's Novels - Duckworth, Alistair M. (Johns Hopkins University Press, 1972)
Originally published in 1994. In The Improvement of the Estate, Alistair Duckworth contends that understanding Mansfield Park is fundamental to appreciating Jane Austen's body of work. Professor Duckworth understands Mansfield Park as underscoring the central uniting theme in Austen's work-her concept of the "estate" and its "improvement." The author illustrates Austen's connection to the values of Christian humanism, which she conveys through the uniting theme of estate improvement. According to Duckworth, the estate represents moral and social heritage, so the manner in which individuals seek to improve their estates in Jane Austen's novels represents the direction in which she saw the state and society moving. Finally, Duckworth underscores Austen's awareness of the importance of a society of individuals whose behavior is socially informed.